The elementary school teachers’ ability in adding and subtracting fraction, and interpreting and computing multiplication and division fraction - Hongki Julie (Universitas Sebelas Maret, 2017)
The purpose of this study was to describe the elementary school teachers’ mathematical skills on the numbers, especially fractions after they have participated in a workshop. The teachers’ abilities which would be described by the researcher in this study were the ability to interpret, to order, to add and subtract, to interpret the meaning of the multiplication and division, to multiply and divide, and to make problems about fractions. In this paper, the author just only would describe the teachers’ mathematical skills in adding and subtracting two fractions, interpreting the multiplication and division of two fractions, multiplying and dividing two fractions. This capability was described base on the results of a test given to teachers after they have attended the workshop. Research subjects in this study were 17 Kanisius Demangan elementary school teachers at Yogyakarta. Of the 17 teachers, 16 teachers could add and subtract two fractions. Six teachers of 17 teachers could interpret what was the meaning of multiplication of two fractions. One teacher could interpret what was the meaning of division of two fractions. All of the teachers could divide two fractions. Sixteen teachers of 17 teachers could multiply two fractions.